2010
DOI: 10.1177/1077801210363539
|View full text |Cite
|
Sign up to set email alerts
|

At the Intersection of Interpersonal Violence, Masculinity, and Alcohol Use: The Experiences of Heterosexual Male Perpetrators of Intimate Partner Violence

Abstract: This article examines the relationship between violence, masculinity, and alcohol use among heterosexual, economically disadvantaged, and primarily Black men officially identified as batterers. Violence occurred against intimates and strangers. Alcohol use coupled with violence against intimates and violence against others (e.g., strangers) appeared to be used for masculinity construction. The use of alcohol before and during assaultive behavior combined with the use of violence symbolized dominance and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 41 publications
1
74
0
12
Order By: Relevance
“…Previous research on actual violence lends credence to this prediction (Atkinson et al, 2005;Maass et al, 2003;Macmillan & Gartner, 1999;Messerschmidt, 2000;Perlata et al, 2010).…”
Section: Social Identity Theory and Threats To Social Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on actual violence lends credence to this prediction (Atkinson et al, 2005;Maass et al, 2003;Macmillan & Gartner, 1999;Messerschmidt, 2000;Perlata et al, 2010).…”
Section: Social Identity Theory and Threats To Social Identitymentioning
confidence: 99%
“…Besides the effect of alcohol consumption (e.g., Abbey, Buck, Zawacki, & Saenz, 2003) and prevention programs (e.g., Foubert & Perry, 2007), few studies have examined the construction of attitudes regarding sexual aggression as part of an interactional process subject to change in response to contextual or situational forces. Given the lack of information about processes shaping the formation of attitudes about date rape and sexual coercion, and recent literature that suggests men who harm women might do so when their sense of masculinity is threatened (Atkinson, Greenstein, & Lang, 2005;Maass, Cadinu, Guarnieri, & Grasselli, 2003;Macmillan & Gartner, 1999;Messerschmidt, 2000;Perlata, Tuttle, & Steele, 2010), we conducted an experiment to evaluate the claim that threatened gender identity affects individuals' views of heterosexual male-on-female sexual aggression. Based on social identity theory (Hogg, 1992;Hogg & Abrams, 1988;Tajfel & Turner, 1979), we anticipate that gender identity threats will lead men to view female victims as more responsible in these settings, while women will view male perpetrators as more responsible.…”
mentioning
confidence: 99%
“…Con el fin de explicar la relación entre consumo de alcohol y violencia contra la mujer en las relaciones de pareja, se considera que el consumo de alcohol se vincula con otro tipo de variables, que a su vez pueden actuar como factores de riesgo o protectores ante la conducta agresiva (Peralta, Tuttle y Steele, 2010). En este sentido, se ha relacionado el consumo de alcohol con variables individuales y contextuales.…”
unclassified
“…One recent study by John et al [29], using an in-depth assessment of gender as part of an alcohol treatment study, suggested that levels of psychological adherence to either masculinity or femininity were more important than biological sex in terms of measured outcomes. A few researchers have begun to examine whether alcohol-related violence is an expression of masculinity [61] or a form of compensation for deficient masculinity [49]. We argue that asking a respondent about their sex (male or female) is not an adequate measure of gender.…”
Section: Gender Versus Sex In Alcohol Use Researchmentioning
confidence: 98%